Activities of the wintering party of the 24th Japanese Antarctic Research Expedition in 1983-1984 - Shinji Mae (National Institute of Polar Research, 1990)
The wintering party of the 24th Japanese Antarctic Research Expedition consisting of 35 personnel carried out routine observations and research activities at Syowa and Mizuho Stations, along the coast of Lutzow-Holm Bay and in the area of East Queen Maud Land from January 1983 to January 1984. The main research activities at Syowa Station were coordinated observations of the polar middle atmosphere and marine biological production, which were performed as part of the International Middle Atmosphere Program (MAP) and the Biological Investigations of Marine Antarctic Systems and Stocks (BIOMASS). In addition to these activities at Syowa Station, survey trips for environmental research were carried out at short intervals along the coast of Lutzow-Holm Bay. Glaciological studies were carried out as part of the International Antarctic Glaciological Project (IAGP), at Mizuho Station and along the traverse routes to the Sor Rondane Mountains in East Queen Maud Land. The 411.1 m deep ice-core drilling was completed at Mizuho Station.